2006
DOI: 10.1111/j.1365-2982.2006.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of subclasses of human colonic myenteric neurons by immunoreactivity to Hu, choline acetyltransferase and nitric oxide synthase

Abstract: An accurate method to count human enteric neurons is essential to develop a comprehensive account of the classes of nerve cells responsible for gut function and dysfunction. The majority of cells in the enteric nervous system utilize acetyl choline, or nitric oxide, or a combination of these, as neurotransmitters. Antisera raised against the RNA-binding protein Hu, were used to identify nerve cell bodies in whole mounts of the myenteric plexus of human colon, and then were utilized to analyse cells immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
72
5
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 65 publications
18
72
5
2
Order By: Relevance
“…Neuronal protein HuC/HuD (HuC/D) monoclonal (clone 16A11) antibody labeled neuronal cell nuclei and perikarya, recognizing an epitope within the carboxyterminal domain of HuD (Marusich et al, 1994). Staining pattern of cellular morphology and distribution is the same as previously described (Lin et al, 2002;Murphy et al, 2007). The staining pattern of biotin-conjugated HuC/D monoclonal antibody is identical to that of the unconjugated antibody.…”
Section: Antibody Characterizationmentioning
confidence: 81%
See 2 more Smart Citations
“…Neuronal protein HuC/HuD (HuC/D) monoclonal (clone 16A11) antibody labeled neuronal cell nuclei and perikarya, recognizing an epitope within the carboxyterminal domain of HuD (Marusich et al, 1994). Staining pattern of cellular morphology and distribution is the same as previously described (Lin et al, 2002;Murphy et al, 2007). The staining pattern of biotin-conjugated HuC/D monoclonal antibody is identical to that of the unconjugated antibody.…”
Section: Antibody Characterizationmentioning
confidence: 81%
“…clonal NSE antibody used for the present work recognizes a 48-kDa protein (Marangos et al, 1975) and, as detailed in Results, shows the same pattern of cellular morphology and distribution as previously reported for the ENS (Parr and Sharkey, 1994;Murphy et al, 2007). Neuronal protein HuC/HuD (HuC/D) monoclonal (clone 16A11) antibody labeled neuronal cell nuclei and perikarya, recognizing an epitope within the carboxyterminal domain of HuD (Marusich et al, 1994).…”
Section: Antibody Characterizationmentioning
confidence: 82%
See 1 more Smart Citation
“…This challenge was taken by Jabari et al (2011) who examined surgically removed megacolonic segments of four patients and determined the population of myenteric neurons containing either choline acetyltransferase (ChAT, for cholinergic neurons) or neuronal nitric oxide synthase (NOS, for nitrergic neurons). Previous studies have shown that most myenteric neurons contain either ChAT or NOS in a largely quantitative balanced ratio (Beck et al 2009;Murphy et al 2007). The third immunohistochemically used marker was against the panneuronal human neuronal protein Hu C/D, that binds to the whole neuron population (Beck et al 2009;Ganns et al 2006;Phillips et al 2004).…”
Section: Enteric Nervous Systemmentioning
confidence: 99%
“…In many regions of the gastrointestinal tract the inhibitory reflex is required for the passage of fecal material and the final motor neurons of the reflex are enteric inhibitory, primarily nitrergic, the neuronal nitric oxide synthase positive (nNOS +) neurons [18]. Most human myenteric neurons are either nitrergic or cholinergic [19,20]. The primary neurotransmitter is Ach in the enteric excitatory muscle motor neuron [21][22][23], ascendant and descendants' interneurons [21,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%